A systematic review and meta-analysis of Liuzijue in stable patients with chronic obstructive pulmonary disease - Lu Xiao; Hongxia Duan; Peijun Li; Weibing Wu; Chunlei Shan; Xiaodan Liu (BMC, 2020)
Abstract Background To investigate the effectiveness of Liuzijue exercise on chronic obstructive pulmonary disease (COPD) in the stable phase. Methods We searched six electronic bibliographic databases (PubMed, EMBASE, The Cochrane Library, Web of Science, CNKI, and Wan Fang Data) from inception to August 2018. Randomized controlled trials (RCTs) were included if they evaluated the effect of Liuzijue exercise on stable COPD. Cochrane Collaboration risk-of-bias tool (Cochrane Handbook 5.1.0) was used to assess the risk of bias of included RCTs. Meta-analysis was performed using the Review Manager software (RevMan V.5.3.5) provided by the Cochrane Collaboration. Outcomes assessed included dyspnea, exercise capacity, lung function, and quality of life. Results Fourteen RCTs involving 920 stable COPD patients were included in this systematic review and meta-analysis. The control groups received usual care. The average number of training sessions per participant was 9.3 per week, and the average length of these training sessions was 31.6 min per week. Training duration varied from 3 to 12 months. Meta-analysis results showed that Liuzijue exercise can effectively improve patients' Modified Medical Research Council Dyspnea Scale scores (MD = − 0.73, 95% CI: − 1.13 to − 0.33, P < 0.05), 6MWD (MD = 17.78, 95% CI: 7.97 to 27.58, P < 0.05), forced expiratory volume in one second (FEV1) (MD = 0.23, 95% CI: 0.07 to 0.38, P < 0.05), the percentage of predicted values of FEV1 (FEV1%pred) (MD = 7.59, 95% CI: 2.92 to 12.26, P < 0.05), FEV1/FVC (Forced vital capacity) ratio (MD = 6.81, 95% CI: 3.22 to 10.40, P < 0.05), Quality of life: St. George's Respiratory Questionnaire total score (MD = − 9.85, 95%CI: − 13.13 to − 6.56, P < 0.05), and Chronic Obstructive Pulmonary Disease Assessment Test score (MD = − 2.29, 95%CI: − 3.27, − 1.30, P < 0.05). Conclusion Evidence from meta-analysis suggested that Liuzijue exercise could improve dyspnea, exercise endurance, lung function, and quality of life for stable COPD patients. However, owing to the methodological bias and the placebo effect of Liuzijue exercise, there is a need for further research to confirm these findings. Trial registration PROSPERO (ID: CRD42019130973 ).